2020
DOI: 10.1007/s00382-020-05279-2
|View full text |Cite|
|
Sign up to set email alerts
|

Further inquiry into the interaction between the winter North Pacific storm track and the East Asian trough

Abstract: Based on the daily ERA-Interim reanalysis, interactions between the winter North Pacific storm track (WNPST) and the East Asian trough (EAT) on the interannual scale are further explored from the perspective of energy conversion and the simplified quasi-geostrophic potential vorticity equation. There is a prominent out-of-phase relationship between the EAT and WNPST on the interannual scale. It is baroclinic energy conversion rather than barotropic energy conversion that is the main physical process that the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…We find that the strength and position of the East Asian trough (Gong et al., 2014; Leung & Zhou, 2015) are faithfully reproduced by FGOALS‐f3‐L. Previous studies identified that there is an interaction between the East Asian trough and the winter NPST and that an enhanced East Asian trough attenuates the winter NPST (Song et al., 2016; Yang et al., 2020b). More specifically, the intensified East Asian trough accompanied by the strengthened East Asian winter monsoon (Wang & Chen, 2010) guides the cold air behind the trough southward, which weakens the winter NPST by impacting the atmospheric baroclinicity at higher latitudes (Lee et al., 2010; Song et al., 2016).…”
Section: Possible Physical Mechanisms Explaining the Altered Winter Npstsupporting
confidence: 62%
“…We find that the strength and position of the East Asian trough (Gong et al., 2014; Leung & Zhou, 2015) are faithfully reproduced by FGOALS‐f3‐L. Previous studies identified that there is an interaction between the East Asian trough and the winter NPST and that an enhanced East Asian trough attenuates the winter NPST (Song et al., 2016; Yang et al., 2020b). More specifically, the intensified East Asian trough accompanied by the strengthened East Asian winter monsoon (Wang & Chen, 2010) guides the cold air behind the trough southward, which weakens the winter NPST by impacting the atmospheric baroclinicity at higher latitudes (Lee et al., 2010; Song et al., 2016).…”
Section: Possible Physical Mechanisms Explaining the Altered Winter Npstsupporting
confidence: 62%
“…In fact, apart from the meridional dipole of anomalous PST related to the subtropical jet, there is a meridional dipole of anomalous upper‐level zonal wind associated with the PST (Figure S2 in Supporting Information ), which can also be found in some previous studies (e.g., Lee et al., 2010; Ma & Zhang, 2018; Yang et al., 2020). For example, by using regionally averaged variances of upper‐tropospheric filtered meridional winds, Lee et al.…”
Section: Revisiting the Relationship Between Upper‐level Subtropical ...supporting
confidence: 81%
“…In addition, they suspected that a pair of storm tracks may only exist at the surface and in the low‐level troposphere. When investigating variations in the PST, most previous studies have regarded the PST as a whole (e.g., Ma & Zhang, 2018; Nakamura et al., 2002; Yang et al., 2020; Zhang & Luo, 2017). Given that the storm source regions of the NPST and SPST are different, we cannot ensure the consistency of the variations in the NPST and SPST.…”
Section: Introductionmentioning
confidence: 99%
“…The energy budget is widely used as a diagnostic tool to investigate regional and global climate variation. Energy conversion is also applied to explain the relation among East Asian trough intensity, atmospheric blocking, and North Pacific storm tracks in winter (Yang et al., 2020, 2021). In addition, enhancement of synoptic temperature variation after 2010 is caused by strengthened baroclinic energy conversion from the mean flow to transient eddies in South China and surrounding regions (Leung et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are interactions among atmospheric eddies, mean westerly flow, and the decadal mode in the North Pacific.The energy budget is widely used as a diagnostic tool to investigate regional and global climate variation. Energy conversion is also applied to explain the relation among East Asian trough intensity, atmospheric blocking, and North Pacific storm tracks in winter (Yang et al, 2020(Yang et al, , 2021. In addition, enhancement of synoptic temperature…”
mentioning
confidence: 99%